Testing the viability of emotions and issue involvement as predictors of CSA response behaviors. Issue 6 (1st November 2020) - Overton, Holly; Choi, Minhee; Weatherred, Jane Long; Zhang, Nanlan
ABSTRACT: Corporate social advocacy (CSA) has become more prominent as companies continue taking stands on politically charged social issues. This study examines emotions and issue involvement as antecedents of theory of planned behavior variables (attitudes, subjective norms, and perceived behavioral control) to predict CSA response behaviors. A survey ( N = 373) was conducted to examine the public's response to a recent CSA example – Nike's ad campaign featuring Colin Kaepernick. Implications for theory and practice are discussed.